Customer satisfaction towards the services provided by POS Malaysia Berhad / Norazilla Abd Aziz - Abd Aziz, Norazilla (Faculty of Business and Management, 2010)
Organizations cannot exist without customers. As such, the customer must be the central focus of the organization. The purpose of this research is to study The Customer Satisfaction towards the services provided by Pos Malaysia Berhad. This research also will determine whether customer is satisfied with service provided by Pos Malaysia Berhad after Pos Malaysia Berhad brings their attention to the recent announcement by the Ministry of Information, Communications and Culture on the increase of the postal rates. Kindly, it is informed that such revision will take effect on 1 July 2010 subject always to the official gazette. In this study, the researcher collects the information from primary data by interview from the Executives and Supervisor in Pos Malaysia Berhad. Researcher also makes observation from website and questionnaire from the customer. Researcher used journal, article and text book as secondary data. This study will help Pos Malaysia Berhad to identify their weakness in order to achieve the high level of customer satisfaction toward the services provided by Pos Malaysia Berhad. This study utilized questionnaire as the instrument for collecting data. Questionnaires have been distributed to 30 respondents and our respondents are from public (customer). In conclusion, the most important services provided by Pos Malaysia Berhad can be identifying. This is important because it will improve the productivity, service quality, and efficiency of Pos Malaysia Berhad (PMB). From the analysis, researcher have identified that the significant relationship between respondents’ profile and type of services.